PEMANTAUAN PERGERAKAN TANAH PADA JEMBATAN TOL SEMARANG–SOLO (JEMBATAN PENGGARON) MENGGUNAKAN GPS–REAL TIME KINEMATIC - Antonius Alex Harmoko; Suryo Hespiantoro (JURNAL GEOMINERBA (JURNAL GEOLOGI, MINERAL DAN BATUBARA), 2019)
According to a report from PT Trans Marga Jateng in March 2011, there was a change in the condition of the Penggaron Bridge located in the Semarang–Solo toll road Km. 20–21. These changes are indicated due to the Landslide, resulting in erosion and subsidence on the east side of the Penggaron bridge. As a result of the ground movement arises fractures in the expansion joint on the right side and there is a decrease in soil. Based on this, monitoring the movement of the soil by studying geological data, the occurrence of soil movements, geomorphology, water, rainfall, land use and installation of stakes. The method used in the form of a sliding stake measured using the Global Position System (GPS) - Real-time Kinematic (RTK) to get the position vector with high accuration. The results show that there are several points on the sliding stakes which show a change between 0.7–69 cm at 6 points of stakes. Horizontal shift shows the direction of the vector to the south and southeast, and vertically the magnitude of the change in peg increase ranges from 2–13 cm and and decrease of stakes around 0.7–17.5 cm for 10 months periods from February until November 2018.